Students’ Perception on E-Portfolio for Assessing Translation Skill - Handayani, Witri; Rozimela, Yenni; Thahar, Harris Effendi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Translation is actually the skill which involve students’ active contribution in the assessing process. Meanwhile, e-portfolio regards as one of the method to achieve students’ active contribution in assessing their own translation works since it not only functions to collect the works electronically but can also function to show the sequence of works improvement. The aim of this study is to investigate students’ perception on e-portfolio for assessing their translation skill. It was also intended to discover application preference to apply the e-portfolio method of assessment. The participants of the study are 49 English Department students enrolled in the third year. The data was collected by using questionnaire in the form of closed and open questionnaires. The results indicate that the participants generally prefer to be evaluated by the e-portfolio assessment. Most of them believed that e-portfolio assessment improved their translation quality and enhanced their motivation and the application they chose to apply the e-portfolio is the free application which can be accessed anywhere.